2019
DOI: 10.3389/fneur.2019.00084
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Sodium MRI as a Biomarker for Neurodegeneration and Neuroinflammation in Multiple Sclerosis

Abstract: In multiple sclerosis (MS), experimental and ex vivo studies indicate that pathologic intra- and extracellular sodium accumulation may play a pivotal role in inflammatory as well as neurodegenerative processes. Yet, in vivo assessment of sodium in the microenvironment is hard to achieve. Here, sodium magnetic resonance imaging (23NaMRI) with its non-invasive properties offers a unique opportunity to further elucidate the effects of sodium disequilibrium in MS pathology in vivo in addition to regular proton bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 117 publications
1
58
0
Order By: Relevance
“…, in which all Na + is aqueous, whereas some Na + ions in tissue can be bound. These observations are in agreement with prior 23 Na-MRI results (Driver et al, 2020;Gilles et al, 2017;Huhn et al, 2019;Meyer et al, 2019;Ridley et al, 2018).…”
Section: In Vitro Studies For Mechanistic Separation Of 23 Na Peakssupporting
confidence: 91%
“…, in which all Na + is aqueous, whereas some Na + ions in tissue can be bound. These observations are in agreement with prior 23 Na-MRI results (Driver et al, 2020;Gilles et al, 2017;Huhn et al, 2019;Meyer et al, 2019;Ridley et al, 2018).…”
Section: In Vitro Studies For Mechanistic Separation Of 23 Na Peakssupporting
confidence: 91%
“…In the brain, 23 Na‐MRI has been exploited extensively for a variety of applications such as stroke, neurodegenerative diseases, and cancer 2,3 . For example, in multiple sclerosis (MS) patients, an increase in the tissue sodium concentration (TSC) was found 4‐6 . Furthermore, the TSC has been quantified in malignant tumors, where significant differences between tumors and contralateral brain tissue have been observed 7 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For example, in multiple sclerosis (MS) patients, an increase in the tissue sodium concentration (TSC) was found. [4][5][6] Furthermore, the TSC has been quantified in malignant tumors, where significant differences between tumors and contralateral brain tissue have been observed. 7 Additionally, it has been shown that sodium MRI can predict tumor chemo-resistance before therapy and can, therefore, be a key component of individualizing cancer treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed these findings. [115][116][117][118] In order to obtain more specific information, Petracca et al used a method that combined SQ and TQF MRI, to quantify TSC and the intracellular sodium molar fraction (ISMF) and then derived ISC and ISVF, an indirect measure of ESC. The results generated from 19 relapsing-remitting MS patients and 17 heathy controls showed that global TSC and ISC evaluated in GM were higher, while GM and WM ISVF (indirect measure of extracellular sodium concentration) were lower in patients compared with healthy controls.…”
Section: Ischemic Strokementioning
confidence: 99%